TEOLOGI DEUTERONOMISTIS AMOS 4:1-3 BAGI KEHIDUPAN SOSIAL UMAT - Maria Evvy Yanti (Jurnal Teologi Cultivation, 2018)
AbstrakTujuan penulisan artikel ialah menemukan karakter teologi Deuteronomistis dari Amos 4:1-3. Materi ini merupakan orasi Amos yang dituliskan oleh para redaktur. Teks ini sarat dengan pengajaran untuk mempraktikkan ketaatan dan ketekunan melakukan kehendak Allah. Metodologi penelitian yang digunakan dengan mengadaptasi pendekatan kualitatif termasuk: sejarah sosial, kritik redaksi, kritik teks dan analisis refleksi teologi dari Amos 4:1-3 yang memiliki karakter Deuteronomistic. Hasil dari penelitian Amos 4:1-3 untuk menaati dan mengembangkan karakter kehidupan sesuai kehendak Allah. Hasil dari penelitian ini menunjukkan bahwa teologi Deuteronomistis dalam Amos 4:1-3 menjadi pengajaran kebenaran Allah yang teraktualisasi melaluikehidupan sosial umat.Kata-kata kunci: orasi, deuteronomistis, sejarah sosial, sejarah redaksi, ketaatanAbstractThe research is intended to find out the character of Deuteronomistic Theology from Amos 4:1-3 for the social life of people. This material is an oration delivered by Amos which be told from redaktor. This oration is God’s Judgement becouse the wrong behaviors people in the social life aspects. This texts is full of dairy God’s will. Research methodology used in this research adopts qualitative approach including: sosial history, redaction criticism, text criticism and analysis of theological reflection ofDeuteronomistic of Amos 4:1-3 to obey and develop the character life in God’s will. The research suggets there are the character of Deuteronomistic theology in Amos 4:1-3 should be on God’s truth teaching through practise of social human life.Key Words: oration, The Deuteronomistic theology, social history, redaction history, obedienc